136 Mycotoxin Contamination in United States Corn and Corn DDGS from 2019 and 2020 Harvest - Zheng, Lan (J Anim Sci, 2021)
Mycotoxins are harmful secondary fungal metabolites central to food and feed safety management. These toxins are detrimental to animal health and even at low levels can compromise performance. Focus on clinical signs like decreased feed intake and vomiting overlook significant impacts of mycotoxicosis, including increased disease incidence and severity, immune dysfunction, inflammation, and modulation of the gastrointestinal environment. The objective of this study was to determine the effect of harvest year on five major mycotoxin groups: aflatoxins (Afla), type A trichothecenes (A-Trich), type B trichothecenes (B-Trich), fumonisins (FUM), and zearalenone (ZEN) in corn and corn DDGS samples. For each mycotoxin group within ingredient, 2019 harvest (329 corn and 20 corn DDGS) were compared with 2020 harvest (27 corn and 21 corn DDGS). Data were analyzed using GLIMMIX procedure of SAS with harvest year as fixed effect and sample as the experimental unit. Average B-Trich and FUM contamination levels in corn are significantly (P < 0.05) affected by harvest year. However, B-Trich levels remained consistent, whereas FUM decreased (P < 0.05) from 2019 to 2020. Contamination levels in corn for Afla, A-Trich, and ZEN have remained consistent (P > 0.05) from 2019 to 2020. In corn DDGS, B-Trich contamination level was decreased (P < 0.05) from 2019 to 2020, whereas FUM and ZEN contamination levels remained similar (P > 0.05). The 2020 crop risk profile is likely to change as the sample pool expands. A combination of hot weather, storm events, and drought during the 2020 growing season resulted in crop stress and damage, ultimately leading to grain quality and mycotoxin contamination concerns. Due to the continued risk of mycotoxin co-occurrence, expanding mitigation strategies beyond adsorption by mycotoxin deactivation with biotransformation and additional support of immune and liver function is essential. [Image: see text] [Image: see text]